Estrogens counteract tributyltin-induced toxicity in the rat islets of Langerhans - Ghaemmaleki, Faezeh (Heliyon, 2020)
BACKGROUND: Tributyltin (TBT) is known as an endocrine disruptor able to interfere with estrogen receptors (ERs) leading to toxic effects on the related endocrine pathways. TBT is an obesogen, reported to disrupt glucose homeostasis leading to diabetes. The aim of this study was to assess the influence of TBT and β-estradiol on the pancreatic islets of Langerhans in simultaneous exposures. EXPERIMENTAL: Pancreatic islets of 15 male rat were isolated and exposed to TBT (10 μM), β-estradiol, and TBT plus β-estradiol for 24 h. Therewith, cellular viability, oxidative stress, apoptosis, and insulin secretion markers were investigated. RESULTS: TBT decreased the viability and increased the apoptosis, reactive oxygen species, and insulin secretion TBT led to increased amounts of apaptosis, reactive oxygen species (ROS), and insulin secretion in pancreatic islets; however, cellular viability was reduced. Co-exposure with β-estradiol ameliorated the entire mentioned variables near to the control level. CONCLUSION: These results showed that β-estradiol protect pancreatic islets of Langerhans against TBT-induced toxicity by counteracting oxidative stress and apoptosis as well as insulin secretion. In this way, it is postulated that pancreatic ER pathways particularly in β-cells might be the determinant target of toxic effects of xenoestrogens like TBT. Hence, evaluation of xenoestrogens-induced ER dysfunction in the endocrine pancreas can be helpful in diabetic risk assessment of these contaminants. Pharmacological modifications of ER pathway in the β-cells seems promising for better management of diabetes.